THE INFLUENCE OF TRAINING AND PERSONALITY ON EMPLOYEE JOB SATISFACTION WITH MOTIVATION AS AN INTERVENING VARIABLE AT PT BANK PEMBANGUNAN DAERAH PAPUA, SENTANI BRANCH OFFICE - Rahmawaty, Ika; Razak, Mashur; Megawaty, Megawaty (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to examine the influence of training and personality on employee job satisfaction with motivation as an intervening variable at PT Bank Pembangunan Daerah Papua, Sentani Branch Office. The research was conducted at PT Bank Pembangunan Daerah Papua, Sentani Branch Office, over a period of two months, from May to June 2025. The population and sample in this study consisted of 70 employees from PT Bank Pembangunan Daerah Papua, Sentani Branch. This study used a survey method by distributing questionnaires to the research subjects. The statistical method used to test the hypotheses was Partial Least Squares (PLS) with the help of the SmartPLS application. The results of the analysis showed that training has a positive and significant effect on motivation; personality has a positive and significant effect on motivation; training has a positive and significant effect on job satisfaction; personality has a positive but not significant effect on job satisfaction; employee motivation has a positive and significant effect on job satisfaction; training has a positive and significant effect on job satisfaction through motivation as an intervening variable; and personality has a positive and significant effect on job satisfaction through motivation as an intervening variable.